The Role of E-Satisfaction on Repurchase and E-Wom Intention on The Costumers of Food Products By Local Micro and Small Businesses on The Digital Platforms - Santoso, Enrico Verrell; Ardianti, Retno (School of Business, IPB University (SB-IPB), 2023)
Despite the increasing popularity of online food delivery services, extant studies have not looked at factors that contribute to customers’ willingness to repurchase and recommend food products by local micro and small businesses to other app users. Meanwhile, the topic is essential given that food products from local micro and small businesses face direct competition with well-known products from large corporations on digital platforms. Therefore, this study aims to examine the role of food quality, price fairness and perceived value on e-satisfaction and the role of e-satisfaction on the repurchase and e-WOM intention of the customers of food products by local micro and small businesses. Using data from 100 customers of local micro and small businesses on the popular food delivery applications in Pekalongan, Indonesia and employing Partial Least Square (PLS) in our data analysis, our results show that food quality and price fairness have a significant effect on e-satisfaction. In addition, our findings show that e-satisfaction has a positive and significant effect on repurchase intention, but it shows a non-significant positive effect on e-WOM intention. Overall, our findings suggest that on digital platforms, gaining customer satisfaction about the product's quality and the price's fairness may not be enough, as it does not indicate a significant relationship with the willingness of the customers to recommend it to other app users. Keywords: food quality, price fairness, perceived value, e-satisfaction, repurchase intention, e-WOM intention